1976
DOI: 10.1107/s0021889876011114
|View full text |Cite
|
Sign up to set email alerts
|

Crystal data for Cs2HfCl6

Abstract: The crystal structure of Cs2HfC16 was determined to be cubic, Fm3m, similar to K2PtC16, with parameters: a0 = 10.42+0.01 A, and u=0.247_+0.003. Powder diffraction data on which the determination was based are given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Our work focuses on the ceramic CHC crystal. The crystal structure of CHC is cubic and isostructural to that of K 2 PtCl 6 making [ 15 ] a good candidate for ceramic research. As a single crystal, it is non‐hygroscopic, exhibits no intrinsic radioactivity, and has a high Z eff number of 58.…”
Section: Introductionmentioning
confidence: 99%
“…Our work focuses on the ceramic CHC crystal. The crystal structure of CHC is cubic and isostructural to that of K 2 PtCl 6 making [ 15 ] a good candidate for ceramic research. As a single crystal, it is non‐hygroscopic, exhibits no intrinsic radioactivity, and has a high Z eff number of 58.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, at the melting point of Cs 2 HfCl 6 (850 °C) HfCl 4 intensively sublimates (sublimation temperature at atmosphere pressure is 315 °C [7]), therefore, HfCl 4 is concentrated in the free space of the boule. It was observed that the boule composition often contained the CsCl impurity phase from the reaction mixture [1,3,8].…”
Section: Introductionmentioning
confidence: 99%
“…The crystal structure of Cs 2 HfCl 6 was first refined in 1976 from the powder X-ray diffraction (XRD) data in the cubic space group 3 Fm m (No. 225), lattice parameter a = 10.42(1) Å [8]. As input information for the refinement we utilized structural data for potassium chloroplatinate K 2 PtCl 6 [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations